Comprehensive CFD analysis of base pressure control using quarter ribs in sudden expansion duct at sonic Mach numbers - Ambareen Khan; Abdul Aabid; Sher Afghan Khan; Mohammad Nishat Akhtar; Muneer Baig (International Journal of Thermofluids)
This study aims to assess the effect of rib size, shape, and location in a suddenly expanded flow at sonic Mach number. Flow from a converging nozzle is exhausted into a larger area of duct diameter of 18 mm. The geometric parameters considered are the area ratio, duct length, rib radius, and inertia parameters, which are considered the level of expansion at critical Mach number. In the present study, duct lengths were from 1D to 6D, rib radii considered were 1 mm to 3 mm, and rib locations were 0.5D, 1D, 1.5D, 2D, and 3D. Results show that when the ribs are placed near the reattachment point with a 3 mm radius, they are efficient and capable of reducing the suction in the recirculation zone and the base pressure, which was lower than the ambient pressure in the absence of ribs, is assorted larger than the back pressure. If the requirement is to equate the pressure at the base to ambient pressure, then a 2 mm radius is the right choice. Furthermore, the 1 mm rib cannot reduce the suction in the base region, and base pressure remains sub-atmospheric for the entire range of rib locations, as well as the NPRs of the present study. When the orientation of the ribs is changed, and the flow interacts with the flat surface instead of the curved surface, there is a marginal change in the flow pattern, and there is no significant change in the base pressure values.